The Role of Socialization Agents in Religious Adulthood Blind Persons (Case Study at Raudlatul Makhfufuin Foundation, Tangerang Selatan) - sapto Wibowo (Trigin Publisher, 2020)
This study aims to obtain a concrete picture of the role of socialization agents in the religiosity of adult blind people. Blindness is divided into two, namely totally blind (total blind) and low vision (who still has vision but is low). The causes of blindness can be congenital or genetic, or caused by external or exogenous factors, such as accidents, illness, and so on. Meanwhile, socialization agents consist of family, playmates, schools and mass media. These socialization agents are parties who play a role in the process of introducing someone to their environment, or in other words those who help someone to socialize. The object of this research is the informants who experience blindness when they are adults. This means,blind since birth. Based on the results of the study, it can be concluded that the role of socialization agents in providing religious knowledge is quite large, especially the role of socialization agents for playmates and the mass media. While the play a major role in providing motivation and enthusiasm for life for adults with visual impairments are family and playmates. With the increase in religious knowledge and enthusiasm for life gained by the informants through socialization agents, they are more enthusiastic and confident in living life as well as possible.